Unveiling the novel role of circadian rhythms in sepsis and septic shock: unexplored implications for chronotherapy - Ramsay, Stewart D.; Nenke, Marni A.; Meyer, Emily J.; Torpy, David J.; Young, Richard L. (Frontiers in Endocrinology, 2025)
Circadian rhythms are critical to coordinating body processes to external environmental cues, such as light and feeding, to ensure efficiency and maintain optimal health. These rhythms are controlled by ‘clock’ transcription factors, such as Clock, Bmal1, Per1/2, Cry1/2, and Rev-erbs, which are present in almost every tissue. In modern society, disruptions to normal circadian rhythms are increasingly prevalent due to extended lighting, shift work, and long-distance travel. These disruptions misalign external cues to body processes and contribute to diseases such as obesity and non-alcoholic fatty liver disease. They also exacerbate pre-existing health issues, such as depression and inflammatory bowel disease. The normal inflammatory response to acute infection displays remarkable circadian rhythmicity in humans with increased inflammatory activity during the normal night or rest period. Severe bloodborne infections, exemplified in sepsis and the progression to septic shock, can not only disrupt the circadian rhythmicity of inflammatory processes but can be exacerbated by circadian misalignment. Examples of circadian disruptions during sepsis and septic shock include alteration or loss of hormonal rhythms controlling blood pressure and inflammation, white blood cell counts, and cytokine secretions. These changes to circadian rhythms hinder sepsis and septic shock recovery and also increase mortality. Chronotherapy and chronopharmacotherapy are promising approaches to resynchronise circadian rhythms or leverage circadian rhythms to optimise medication efficacy, respectively, and hold much potential in the treatment of sepsis and septic shock. Despite knowledge of how circadian rhythms change in these grave conditions, very little research has been undertaken on the use of these therapies in support of sepsis management. This review details the circadian disruptions associated with sepsis and septic shock, the influence they have on morbidity and mortality, and the potential clinical benefits of circadian-modulating therapies.